Connecting Alzheimer’s Disease With Diabetes Mellitus Through Amyloidogenic Evolvability - Ho, Gilbert; Takamatsu, Yoshiki; Wada, Ryoko; Sugama, Shuei; Waragai, Masaaki; Takenouchi, Takato; Masliah, Eliezer; Hashimoto, Makoto (Frontiers in Aging Neuroscience, 2020)
Type 2 diabetes mellitus (T2DM) has been clearlylinked to oxidative stress and amylin amyloidosis in pancreatic β-cells. Yet despite extensive investigation, the biological significance of this is not fully understood. Recently, we proposed that Alzheimer’s disease (AD)-relevant amyloidogenic proteins (APs), such as amyloid-β (Aβ) and tau, might be involved in evolvability against diverse stressors in the brain. Given the analogous cellular stress environments shared by both T2DM and AD, the objective of this study is to explore T2DM pathogenesis from the viewpoint of amyloidogenic evolvability. Similar to AD-related APs, protofibrillar amylin might confer resistance against the multiple stressors in β-cells and be transmitted to offspring to deliver stress information, in the absence of which, type 1 DM (T1DM) in offspring might develop. On the contrary, T2DM may be manifested through an antagonistic pleiotropy mechanism during parental aging. Such evolvability-associated processes might be affected by parental diabetic conditions, including T1DM and T2DM. Furthermore, the T2DM-mediated increase in AD risk during aging might be attributed to an interaction of amylin with AD-related APs through evolvability, in which amylin protofibrillar formation presumably caused by adiponectin (APN) resistance could increase protofibril formation of AD-related APs in evolvability and subsequently lead to T2DM promotion of AD through antagonistic pleiotropy in aging. This suggests that targeting APN combined with an anti-T2DM agent might be therapeutic against neurodegeneration. Collectively, T1DM and T2DM might be linked through amylin evolvability, and a better understanding of amyloidogenic evolvability might also reveal clues to therapeutic interventions for AD comorbid with T2DM.